2005
DOI: 10.2337/diabetes.54.5.1552
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Antipsychotics on Carbachol-Enhanced Insulin Secretion From Perifused Rat Islets

Abstract: Treatment with the atypical antipsychotics olanzapine and clozapine has been associated with an increased risk for deterioration of glucose homeostasis, leading to hyperglycemia, ketoacidosis, and diabetes, in some cases independent of weight gain. Because these events may be a consequence of their ability to directly alter insulin secretion from pancreatic ␤-cells, we determined the effects of several antipsychotics on cholinergic-and glucose-stimulated insulin secretion from isolated rat islets. At concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 47 publications
3
73
3
Order By: Relevance
“…Atropine, an agent that blocks muscarinic receptors, decreased glucoseinduced insulin release. It has been reported that the inhibitory effect of clozapine (which strongly binds to muscarinic M3 receptor) or atropine is not observed under non-stimulatory glucose concentration, but is evident at 7.0 mmol L -1 glucose (28). Confi rming the role of ACh, our data indicate that atropine reduced 8 mmol L -1 glucose-stimulated insulin secretion when used alone, but, interestingly, it potentiated the diazinon-induced effect (Figure 2).…”
Section: Discussionsupporting
confidence: 67%
“…Atropine, an agent that blocks muscarinic receptors, decreased glucoseinduced insulin release. It has been reported that the inhibitory effect of clozapine (which strongly binds to muscarinic M3 receptor) or atropine is not observed under non-stimulatory glucose concentration, but is evident at 7.0 mmol L -1 glucose (28). Confi rming the role of ACh, our data indicate that atropine reduced 8 mmol L -1 glucose-stimulated insulin secretion when used alone, but, interestingly, it potentiated the diazinon-induced effect (Figure 2).…”
Section: Discussionsupporting
confidence: 67%
“…The metabolic dysregulation with atypical antipsychotics occurs even in the absence of underlying disease as recently shown with olanzapine in a dog model [47]. Furthermore, experimental data demonstrated that low concentrations of clozapine and olanzapine can markedly and selectively impair cholinergic-stimulated insulin secretion by blocking muscarinic M2 receptors, which could be one of the contributing factors to their higher risk for producing hyperglycemia and diabetes in humans [48].…”
Section: Underlying Mechanismsmentioning
confidence: 71%
“…In accordance with this view, mice with targeted deletions in the M 3 gene have reduced basal levels of insulin and glucagons. 88 Johnson et al 89 also found that low concentrations of olanzapine and clozapine (but not risperidone or ziprasidone) can markedly and selectively impair cholinergicstimulated insulin secretion by blocking muscarinic M 3 receptors in isolated rat islet cells. In vitro binding and functional data also showed that olanzapine and clozapine, unlike the other two atypical agents or haloperidol, are potent muscarinic M 3 antagonists.…”
Section: Diabetes 62mentioning
confidence: 97%